2004
DOI: 10.1007/s00167-003-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

A computer assisted surgical technique for retrograde autologous osteochondral grafting in talar osteochondritis dissecans (OCD): a cadaveric study

Abstract: This study describes a new method for the treatment of osteochondritis dissecans (OCD) in the medial talar dome. Ten cadaveric lower extremities were used to develop and evaluate a retrograde osteochondral grafting technique applying computer-assisted surgery. With the help of a computed tomography (CT)-based navigation system, a guide wire was placed from the lateral talar process into the posteromedial talar trochlea where OCD lesions are predominantly located. Cannulated reamers and arthroscopic shavers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
13
0
4
Order By: Relevance
“…Retrograde drilling using fluoroscopy has been described in other studies [7,9,10], as well as retrograde drilling using a cast and a CT navigation system [5,6,8,15], with good success, but all included arthroscopic examination of the joint. Bail et al [16] described a novel method for retrograde drilling using MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrograde drilling using fluoroscopy has been described in other studies [7,9,10], as well as retrograde drilling using a cast and a CT navigation system [5,6,8,15], with good success, but all included arthroscopic examination of the joint. Bail et al [16] described a novel method for retrograde drilling using MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde drilling, which leaves the cartilage unharmed, has only been described in a few studies [5][6][7][8][9][10], but success rates are high: 81-100% [8,9,11]. Most studies use arthroscopy as a navigation method for retrograde drilling, but fluoroscopy is used for navigation as well [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Dafür ist aber häufig ein ausgedehnter Zugang mit Osteotomie nötig [19]. Zur genaueren und weniger schädigenden retrograden Bohrung wurde die Computertomographie (CT)-basierte computerassistierte Chirurgie (CAS)-gesteuerte Technik beschrieben [2,7,10,18]. Die derzeit in Anwendung befindlichen dreidimensionalen CT-und Röntgenbildverstärker (BV-2-D)-basierten Navigationssysteme sind in Ihrer Flexibilität (CT) und Visualisierung (BV-2-D) sehr eingeschränkt [13,15].…”
Section: Navigierte Retrograde Anbohrung Bei Osteochondrosis Dissecanunclassified
“…Die Spongiosa kann sehr leicht mit einem manuell geführten 3,5-mm-Bohrer eingestößelt werden Abb. 10 8 Arthroskopische Abschlussbeurteilung. Hierbei insbesondere Überprüfung der Knorpeloberfläche, die in diesem Fall intakt und westlich weniger eindrückbar war als vor der Intervention.…”
Section: Operationsprinzip Und -Zielunclassified
“…The planning consisted of using patient images to manually choose a path for the surgical drill. Another study using the talus found better plug harvesting and placement with computer assist [13]. Computer planning has also been used to match plugs from the femoral condyles to defects in the talus [14].…”
Section: Related Workmentioning
confidence: 99%